Legal Protection Bonda And Bulango Languange : In Reality And Prospect - Nggilu, Novendri; Badu, Lisnawaty Wadju; Imran, Suwitno Yutye (Universitas Negeri Gorontalo, 2021)
72 years independent of Indonesia, the regulation of culture became a